Effect of the Temperature on CO2/Brine/Dolomite Wettability: Hydrophilic versus Hydrophobic Surfaces - Al-Yaseri, A.; Roshan, H.; Zhang, Y.; Rahman, T.; Lebedev, Maxim; Barifcani, Ahmed; Iglauer, Stefan (American Chemical Society, 2017)
The water contact angle in a system of brine (20 wt % CaCl 2 ) and CO 2 was measured on a smooth dolomite surface [root mean square (RMS) surface roughness of 45 nm] with both hydrophilic and hydrophobic behaviors as a function of the pressure (0.1, 5, 10, 15, and 20 MPa) and temperature (308, 323, and 343 K). The experimental results show that the contact angle of brine/CO 2 increases slightly with the temperature when the dolomite surface is hydrophilic but, interestingly, reduces when the surface is hydrophobic. The results also illustrate that the brine/CO 2 contact angles increase with increasing pressure. We interpreted the experimental observations using the concept of alteration in van der Waals potential (substrate surface chemistry) with thermodynamic properties, including pressure and temperature.